The genetic basis of 3-hydroxypropanoate metabolism in Cupriavidus necator H16 - Arenas Lopez, Christian (2018)
There is an increasing need to produce fuels and chemical commodities from renewable resources. Current efforts have been mainly focused on liberating sugars from plant-derived lignocellulosic feedstocks. However, lignocellulosic materials have naturally evolved to resist their microbial and enzymatic degradation and this poses a major problem. Due to these difficulties, alternative feedstocks derived from biomass gasification have recently become a major focus of research. The gasification process generates mixtures of hydrogen, carbon monoxide and carbon dioxide, known as syngas, which can be utilised by some autotrophic bacteria as the sole sources of carbon and energy. Cupriavidus necator strain H16 was chosen as a chassis organism for the current investigation as it can grow to high cell densities on CO2/H2 and, under nutrient limiting conditions, stockpiles huge amounts poly[R-(–)-3-hydroxybutyrate] (PHB). The long term aim of the study was to employ metabolic engineering approaches to re-direct carbon flux so that desirable chemicals are produced instead of PHB. Following the establishment of defined growth media, genetic tools, and DNA delivery methods, the natural resistance of the bacterium to a range of desirable target chemicals was tested and 3-hydroxypropanoic acid (3-HP) identified as a suitable target. However, it was noted that C. necator was able to utilise this compound as the sole source of carbon and energy. Hence, several genes involved in the degradation of 3-HP were identified and inactivated through ORF deletion, resulting in strain CNCA13 unable to grow on this compound. However, this strain was still able to co metabolise 3-HP alongside other carbon sources such as fructose or gluconate, necessitating further investigation, including the introduction of additional gene deletions. Some of these deletions belonged to genes or pathways involved in a reductive route for the assimilation of the compound. The inactivation of one of these candidates over the strain CNCA13 led to prevent the co-assimilation of 3-HP alongside fructose. Following strain development, a heterologous pathway designed to produce 3-HP from actyl-CoA in two enzymatic steps was introduced into the organism. The first committed step in this pathway is the carboxylation of acetyl-CoA to malonyl-CoA, catalysed by the enzyme acetyl-CoA carboxylase (ACC). The second step is the reduction of malonyl-CoA to 3-HP, a conversion catalysed by the bifunctional enzyme malonyl-CoA reductase (MCR) or, in some archaea, by the combination of two monofunctional reductases. Genes encoding ACC subunits and MCRs from different bacteria and archaea were codon-optimised, assembled into functional operons and screened for efficient expression in C. necator H16. All genes were found to be expressed, but production of 3-HP could not be observed, even in strains lacking the ability to produce PHB or to consume 3-HP as the sole source of carbon. Thus, further work is needed to efficiently redirect carbon flux through the generated pathway.